2009
DOI: 10.3164/jcbn.08-162
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Assay for Total Antioxidant Capacity in Human Plasma Using a 96-Well Microplate

Abstract: SummaryIn the present study, we tried to establish an efficient assay for total antioxidant capacity (TAC) in human plasma using a 96-well microplate. TAC was assessed using lag time by antioxidants against the myoglobin-induced oxidation of 2,2'-azino-di(3-ethylbenzthiazoline-6-sulfonic acid (ABTS) with hydrogen peroxide, and expressed as Trolox equivalent. The linearity of the calibration curve with Trolox was maintained with the Trolox concentration range from 2.5 µM to 25 µM (R 2 = 0.997). The assay was ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(63 citation statements)
references
References 34 publications
1
61
1
Order By: Relevance
“…6. The contribution of ABTS assay-microplate in evaluating TAC of our results was in agreement with (Kambayashi et al 2009). In summary, the results of antioxidant scavenging activity by ABTS method showed that CP has the same as the effect of Trolox, against the oxidation of ABTS compared with the negative control as given in Fig.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…6. The contribution of ABTS assay-microplate in evaluating TAC of our results was in agreement with (Kambayashi et al 2009). In summary, the results of antioxidant scavenging activity by ABTS method showed that CP has the same as the effect of Trolox, against the oxidation of ABTS compared with the negative control as given in Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the accuracy of these assays remains relatively ambiguous. An efficient assay for the assessment of TAC was currently developed and validated using a 96-well microplate (Kambayashi et al 2009;Erel 2004;Lussignoli et al 1999). Overall, Cocoa and its derived products (cocoa powder, cocoa liquor and chocolates) contain varied polyphenol contents and possess different levels of antioxidant potentials.…”
Section: Introductionmentioning
confidence: 99%
“…However, WAX treatment significantly ameliorated the depletion of all measured factors compared with the control group (Table 1). TAC is a reliable biomarker of total antioxidant level, and GSH, SOD and catalase are three essential antioxidants or free radical quenchers (Alscher et al, 2002;Beers & Sizer, 1952;Evans & Ellman, 1959;Kambayashi et al, 2009). These data indicated that the hepatoprotective action of WAX is mediated through its effects on the antioxidant system in DMN-induced subchronic liver injury.…”
Section: Resultsmentioning
confidence: 78%
“…The TAC in liver tissue was examined by the method described previously (Kambayashi et al, 2009). The results were expressed as mM equivalent of gallic acid.…”
Section: Determination Of Total Antioxidant Capacity (Tac) Total Glumentioning
confidence: 99%
“…Trolox equivalent performed with the ABTS solution represents an important screening tool for oxidative stressrelated diseases by monitoring plasma TAC (Kambayashi et al, 2009).…”
Section: Discussionmentioning
confidence: 99%